Dielectric, ferroelectric and piezoelectric properties of (Ba0.98−xSrxCa0.02) (Ti0.95Zr0.05)O3 lead-free ceramics - Roy P.K.; Ponraj B.; Varma K.B.R. (My University, 2025)
Piezoelectric compositions associated with the chemical formula (Ba0.98−xSrx Ca0.02)(Ti0.95Zr0.05)O3 where x = 0, 0.05, 0.10 and 0.15, were synthesized successfully via solid-state reaction route. The dielectric, ferroelectric, piezoelectric and strain properties of the ceramics of these compositions were studied. X-ray diffraction studies confirmed the presence of pure tetragonal structure and the cell volume was found to decrease with the increase in Sr content. Scanning electron microscopy showed increase in grain size for Sr doped samples when compared to undoped ceramics. Interestingly, the sample with x = 0.10 mol of Sr content exhibited excellent piezoelectric properties. The polarization and strain behaviour for the aforementioned sample showed high piezoelectric strain of 0.22% at 40 kV/cm. The remnant polarization of 13.45 μC/cm2 associated with high piezoelectric coefficient (d33) of 320 pC/N were obtained for the ceramic with x = 0.10 mol of Sr content. These results confirmed that the (Ba0.88 Sr0.10Ca0.02)(Ti0.95Zr0.05)O3 system is a promising lead-free high piezoelectric strain material for piezoelectric based device applications. © 2017 Elsevier Ltd and Techna Group S.r.l.